Assessment of self-knowledge of diabetic patients about diabetes mellitus in Teresina – PI (Research, Society and Development, 2023)
Diabetes Mellitus (DM) represents a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion or action. The objective was to evaluate the level of self-knowledge about diabetes mellitus of diabetic patients about the disease in Teresina-PI. This is a cross-sectional study with a quantitative approach, carried out through the application of a questionnaire via Google Forms. It was found that 65% of the individuals were female, with a mean age of 56.62 years. About 43.3% knew they had diabetes, 46.7% reported using metformin/others, 36.7% said they had been informed about having/had high blood pressure, cholesterol and being overweight or obese. About 85.0% said they knew that DM causes changes in the feet, and the most mentioned were wounds (36.7%) and loss of sensitivity (25%). 85.7% reported receiving a diet, and 41.7% said they did not follow the diet. 96.7% received guidance on physical activity, however 68.3% did not perform any activity. All patients reported using the medications daily and 58.3% did not have a glucometer. About 96.7% said they did not have their feet evaluated by a doctor, 80% did not check them daily, 60% did not dry their feet, 56.7% walk barefoot, 60% do not wear socks, 71.1% do not use creams or oils on their feet, 55% cut their nails in a straight line and 48.3% cut the calluses on their feet. It was found that knowledge of self-care practices is not a guarantee that the individual will be committed to carrying it out, but the person should be given the opportunity to have access to the range of learning.